PERKEMBANGAN PENDIDIKAN ISLAM DI BRUNEI DARUSSALAM - Feriansyah, Feriansyah (CV. ADIBA ASIHA AMIRA, 2024)
Brunei Darussalam as an Islamic country always follows these developments in order to achieve common goals. However, looking at the reality of what is happening in the country, it still cannot achieve its goals. Improving the education system continues to be developed, changing the curriculum to suit the demands of the times and providing education funding budgets that suit the community, these are things they do continuously. This is all for the sake of creating citizens who have high human resources. History of the Kingdom of Brunei Darussalam The Kingdom of Brunei seen from its history does not have very authentic evidence of its presence, but if we trace it further from historical studies, the existence of the Brunei state can be clearly seen from its system of government from the past and has had an impact in the present, which began from; First, during the Pre-Sultanate era of the country of Brunei which can be seen from the Vijayapura kingdom and the Po-ni kingdom. The presence of the Vijayapura kingdom was based on sources from the Chinese and Indonesian kingdoms that managed the country of Brunei. However, this kingdom did not last long, because it was conquered by Srivijaya, while the Po-ni kingdom controlled Brunei in the 10th century.